Pancreatic circulating tumor cell detection by targeted single-cell next-generation sequencing. (28th November 2020) - Yu, Jun; Gemenetzis, Georgios; Kinny-Köster, Benedict; Habib, Joseph R.; Groot, Vincent P.; Teinor, Jonathan; Yin, Lingdi; Pu, Ning; Hasanain, Alina; van Oosten, Floortje; Javed, Ammar A.; Weiss, Matthew J.; et al.
Abstract: Background and aims: Single-cell next-generation sequencing (scNGS) technology has been widely used in genomic profiling, which relies on whole-genome amplification (WGA). However, WGA introduces errors and is especially less accurate when applied to single nucleotide variant (SNV) analysis. Targeted scNGS for SNV without WGA has not been described. We aimed to develop a method to detect circulating tumor cells (CTCs) with DNA SNVs. Methods: We tested this targeted scNGS method with three driver mutant genes ( KRAS / TP53 / SMAD4 ) on one pancreatic cancer cell line AsPC-1 and then applied it to patients with metastatic PDAC for the validation. Results: All single-cell of AsPC-1 and spiked-in AsPC-1 cells in healthy donor blood, which were isolated by the filtration with size or by flow cytometry, were detected by targeted scNGS method . All blood samples from six patients with metastatic PDAC, for the validation of target scNGS method, showed CTCs with SNVs of KRAS / TP53 / SMAD4 and the positive confirmation of immunofluorescent stainings with Pan-CK/Vimentin/CD45. Four patients with early stage disease, one patient with benign pancreatic cyst and a healthy control sample all showed concordant results between targeted scNGS and CTC enumeration. Conclusions: The novel technique of targeted scNGS for SNV analysis, without pre-amplification, is a promising method for identifying and characterizing circulating tumor cells. Highlights: In patients undergoing resection of PDAC, the detection of CTCs with phenotypic markers has been shown to have prognostic significance. In this study we developed a novel technology of targeted scNGS for the detection of heterogeneous CTCs from patients with PDAC. The technique of highly sensitive targeted scNGS is a promising method for identifying and characterizing circulating tumor cells.